Quantum Learning Model for Enhancing Instructional Capability: A Community Service on Muslims Student Associations Aceh - Muhammad, Syaifullah; Suryani Sentosa, Dewi; Gusti Vonna, Adinda; Ananda, Putri; Muhibbudin (PT Inovasi Pratama Internasional, 2024)
This article discusses challenges in achieving quality education, especially improving teacher quality, learning motivation, and effective communication skills between instructors and students. This phenomenon includes a decrease in learning motivation due to the 'shutdown' of learning, as well as the need for a learning model that can see student potential holistically based on reason and heart. While many instructors do not pay attention to effective learning methods in improving the quality of education, it is necessary to provide a supportive learning environment for all students and how to improve positive communication skills between instructors and students. This community service activity was carried out by lecturers from Syiah Kuala University to the Islamic Student Association (HMI) Aceh. The result of implementing this learning model is to produce increased understanding and strategies in the way of learning, especially to increase learning motivation, academic scores, and positive attitudes toward learning among students. The application of innovative learning models such as the Quantum Learning Model, together with the strengthening of positive communication skills between teachers and students, can be an effective step in improving the quality of education and addressing gaps in achieving educational equity.